2011
DOI: 10.1017/s1742170511000317
|View full text |Cite
|
Sign up to set email alerts
|

Soil fertility and crop yields in long-term organic and conventional cropping systems in Eastern Nebraska

Abstract: Organic agriculture aims to build soil quality and provide long-term benefits to people and the environment; however, organic practices may reduce crop yields. This long-term study near Mead, NE was conducted to determine differences in soil fertility and crop yields among conventional and organic cropping systems between 1996 and 2007. The conventional system (CR) consisted of corn (Zea mays L.) or sorghum (Sorghum bicolor (L.) Moench)-soybean (Glycine max (L.) Merr.)-sorghum or corn-soybean, whereas the dive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
40
1
3

Year Published

2012
2012
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 43 publications
(45 citation statements)
references
References 55 publications
1
40
1
3
Order By: Relevance
“…However, using fresh animal manures to meet all crop nutrient demands can increase groundwater nitrate leaching and surface runoff of P (Kleinman et al, 2002;Basso and Ritchie, 2005). In most cases, it is not recommended that farmers use manure alone to meet crop N demand because over time P will accumulate well beyond crop sufficiency levels and potentially contribute to pollution of surface waters (Wortman et al, 2012a). Instead, best management practices for calculating organic soil amendment rates should include consideration of N/P ratio of the amendment, baseline soil nutrient levels, crop nutrient demands, and potential mineralization rate of the amendment.…”
Section: Core Ideasmentioning
confidence: 99%
See 1 more Smart Citation
“…However, using fresh animal manures to meet all crop nutrient demands can increase groundwater nitrate leaching and surface runoff of P (Kleinman et al, 2002;Basso and Ritchie, 2005). In most cases, it is not recommended that farmers use manure alone to meet crop N demand because over time P will accumulate well beyond crop sufficiency levels and potentially contribute to pollution of surface waters (Wortman et al, 2012a). Instead, best management practices for calculating organic soil amendment rates should include consideration of N/P ratio of the amendment, baseline soil nutrient levels, crop nutrient demands, and potential mineralization rate of the amendment.…”
Section: Core Ideasmentioning
confidence: 99%
“…Manure and compost application to arable soils can lead to long-term increases in plant essential nutrients (e.g., P, K, and Mg; Bulluck et al, 2002;Wortman et al, 2012a), soil organic matter content, aggregate stability, and water-holding capacity (Goyal et al, 1999;Diacono and Montemurro, 2010), and microbial abundance and activity (Goyal et al, 1999;Pérez-Piqueres et al, 2006). Crop yield can also increase over time with regular application of manure or compost to the same fi eld (Jiang et al, 2006), and yields are oft en similar between fi elds with a long-term history of organic soil amendment compared to inorganic fertilization (Edmeades, 2003).…”
mentioning
confidence: 99%
“…This was reflected in improved soil productivity under the organic plots. Wortman et al [23] report a long-term (11-year) cropping systems study in Nebraska, in which the conventional system consisted of fertilized soybean, winter wheat, maize and sorghum, while organic systems utilized composted beef manure (applied once only) in place of fertilizer, or an alfalfa forage, prior to maize and sorghum. At the end of the study (SOC levels were reported for 0-15 cm depth only) treatments had largely equivalent SOC concentrations.…”
Section: Soil Organic Matter Storagementioning
confidence: 99%
“…Indeed as a reflection of this reality on many organic, particularly grain farms, in North America, long-term rotation studies, such as that of Wortman et al [83] (Nebraska); [Entz, personal communication, 2011] (Manitoba); and Lynch et al [106] (Nova Scotia), tend to use manure or compost supplements as an intermittent P source rather than as a routine N source. For example, Wortman et al [23] in Nebraska used composted beef manure (~30 Mg/ha applied once in 11 years) to offset potential P deficiencies in their organic perennial-grains cropping system. While novel organic amendments such as source-separated municipal solid waste (or 'green waste') composts may be an effective source of soil P (and N) supply [106,123], their use remains limited at present.…”
Section: Phosphorusmentioning
confidence: 99%
See 1 more Smart Citation